2002
DOI: 10.1074/jbc.m204943200
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Equilibrium CuB-CO Complex and Functional Implications of the Transient Hemea3 Propionates in Cytochromeba3-CO from Thermus thermophilus

Abstract: 1؉ -CO species and remains unchanged in the pD range 5.5-9.7 indicating that no structural change takes place at Cu B between these states. The implications of these results with respect to proton pathways in heme-copper oxidases are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
146
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(169 citation statements)
references
References 41 publications
22
146
1
Order By: Relevance
“…In particular, binding of CO to this enzyme leads to formation of only 70% of the heme a 3 -CO complex (21,24), with the remaining 30% forming a CuB-CO complex (25). To estimate the extent of NO binding to heme a 3 , the inset of Figure 1B shows the second derivative of the Soret spectra of the unligated and NO-bound forms.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, binding of CO to this enzyme leads to formation of only 70% of the heme a 3 -CO complex (21,24), with the remaining 30% forming a CuB-CO complex (25). To estimate the extent of NO binding to heme a 3 , the inset of Figure 1B shows the second derivative of the Soret spectra of the unligated and NO-bound forms.…”
Section: Resultsmentioning
confidence: 99%
“…However, crystallographic studies using Xe and Kr to map out the O 2 pathway within ba 3 have indicated that there is no straight-access line from Xe1, the site closest to the binuclear cavity, to Cu B , and that Trp229 and His283 appear to form a barrier that O 2 needs to circumvent to access the dinuclear center (21). These observations, together with the long lifetime of the transient Cu B þ -CO complex in ba 3 (14), suggest that Cu B may not necessarily act as an obligatory stop for O 2 entry to heme a 3 in ba 3 -with-CO. In the absence of CO, the entry of O 2 to heme a 3 in ba 3 may or may not involve prior binding to Cu B .…”
Section: µS 48 µS 55 µS 10 Msmentioning
confidence: 92%
“…The obligatory path of CO to and from heme a 3 in the bovine enzyme has been proposed to involve the binding of CO to Cu B þ (13,25), and an analogous mechanism has been postulated for ba 3 (14,26); the O 2 ligand has been proposed to follow the same path (27). However, crystallographic studies using Xe and Kr to map out the O 2 pathway within ba 3 have indicated that there is no straight-access line from Xe1, the site closest to the binuclear cavity, to Cu B , and that Trp229 and His283 appear to form a barrier that O 2 needs to circumvent to access the dinuclear center (21).…”
Section: µS 48 µS 55 µS 10 Msmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of an H-bonded His-411, electron density is pushed into the antibonding * orbitals of Fe(IV)ϭO, weakening the bond, and thus, shifting the Fe(IV)ϭO stretching frequency from 804 to 790 cm Ϫ1 . The details on how the 804 -790 cm Ϫ1 oxoferryl transition is specifically tuned to initiate the H-bonding interaction and whether it is coupled to the heme a 3 -propionatesAsp-H 2 O protonic connectivity, in a similar manner to that found in cytochrome ba 3 from T. thermophilus (69), remain to be determined.…”
Section: Discussionmentioning
confidence: 99%